Induced Resistance to Ustilago maydis in Zea mays Inoculated in Non-Sterile Conditions - Martínez-Soto, Domingo; Ruiz-Herrera, José (International Journal of Biotechnology for Wellness Industries, 2016)
Plants are able to acquire induced resistance to pathogens (priming) by its previous exposure to biotic or abiotic stresses. To analyze whether this process is involved in the maize infection by Ustilago maydis, we have compared the infection occurring in plants inoculated under axenic conditions or in sterile soil to plants grown in non-sterile soil. Our results showed that plants grown under axenic conditions were more susceptible to infection than those inoculated in non-sterile soil. Accordingly, disease symptoms: chlorosis development, anthocyanin production, tumor development, and necrosis, were more and severe in axenic plants. In addition, cell death and reactive oxygen species production, as well as ethylene, were higher in axenic plants. These observations indicate for the first time, that different physical stressors and contact with microorganisms of the environment are responsible for the induction of resistance (priming) in this pathosystem.